Functional Characterization of the Pheophytinase Gene, ZjPPH, From Zoysia japonica in Regulating Chlorophyll Degradation and Photosynthesis - Teng, Ke; Yue, Yuesen; Zhang, Hui; Li, Hui; Xu, Lixin; Han, Chao; Fan, Xifeng; Wu, Juying (Frontiers in Plant Science, 2021)
Pheophytinase (PPH), the phytol esterase, plays important roles in chlorophyll degradation. Nevertheless, little attention has been paid to the PPHs in warm-season grass species, neither its detailed function in photosynthesis has been systematically explored to date. In this study, we isolated ZjPPH from Zoysia japonica, an excellent warm-season turfgrass species. Quantitative real-time PCR analysis and promoter activity characterization revealed the expression of ZjPPH could be induced by senescence, ABA and dark induction. Subcellular localization observation proved ZjPPH was localized in the chloroplasts. Overexpression of ZjPPH accelerated chlorophyll degradation and could rescue the stay-green phenotype of the Arabidopsis pph mutant. Moreover, ZjPPH promoted senescence with accumulation of ABA and soluble sugar contents, as well as the increased transcriptional level of SAG12 and SAG14. Transmission electron microscopy investigation revealed ZjPPH caused decomposition of chloroplasts ultrastructure in stable transformed Arabidopsis. Furthermore, chlorophyll a fluorescence transient measurement analysis suggested ZjPPH suppressed photosynthesis efficiency by mainly suppressing both PSII and PSI. In conclusion, ZjPPH plays important role in chlorophyll degradation and senescence. It could be a valuable target for genetic editing to cultivate new germplasms with stay-green performance and improved photosynthetic efficiency.